Mujeres y empleo extractivo en América Latina - De La Puente Burlando, Lorena (2017)
Women in Latin America tend to bear greatest negative costs due to extractive industries. Mining and hydrocarbons transform the livelihoods of local populations and also, gender roles that condition access to opportunities for men and women. However, gender roles do not only operate in extractive localities. fte same industry is mainly organized around a masculine culture that allows the marginalization of women as their work force. fte case of direct and indirect employment (formal, informal and illegal) is used to present a series of pending questions despite a context of little information available to understand gender impacts of the extractive industry.